2020
DOI: 10.1016/j.ebiom.2020.102833
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar macrophage dysfunction and cytokine storm in the pathogenesis of two severe COVID-19 patients

Abstract: Background:The novel coronavirus pneumonia COVID-19 caused by SARS-CoV-2 infection could lead to a series of clinical symptoms and severe illnesses, including acute respiratory distress syndrome (ARDS) and fatal organ failure. We report the fundamental pathological investigation in the lungs and other organs of fatal cases for the mechanistic understanding of severe COVID-19 and the development of specific therapy in these cases. Methods: The autopsy and pathological investigations of specimens were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
361
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(390 citation statements)
references
References 25 publications
17
361
0
12
Order By: Relevance
“…Further investigation with reverse genetics will clarify this issue and could allow the rapid synthesis of a recombinant SARS-CoV-2 with enhanced virulence ( 21 , 22 ). Additionally, immunostaining results showed that lung club and AT2 cells are major target cells of MASCp6, which is in agreement with previous findings from animal models and COVID-19 patients ( 11 , 23 , 24 ).…”
Section: Discussionsupporting
confidence: 92%
“…Further investigation with reverse genetics will clarify this issue and could allow the rapid synthesis of a recombinant SARS-CoV-2 with enhanced virulence ( 21 , 22 ). Additionally, immunostaining results showed that lung club and AT2 cells are major target cells of MASCp6, which is in agreement with previous findings from animal models and COVID-19 patients ( 11 , 23 , 24 ).…”
Section: Discussionsupporting
confidence: 92%
“…Despite the lack of signi cant differences in lung function-related parameters between anaemic patients and non-anaemic patients in our study, patients with moderate to severe anaemia presented a prominently higher proportion ofdyspnea symptoms and lower levels of PaO 2 and SaO 2 than patients with mild anaemia. As shown in the recent autopsy reports of COVID-19 patients, macrophages, neutrophils, and lymphocytes were observed in alveolar cavities [15] .Since the increasing degree of neutrophilic in ltration was more evident in patients with anaemia, an elevated neutrophilic count might indicate serious pulmonary in ltration of in ammation, which might further degrade lung function.…”
Section: Discussionmentioning
confidence: 87%
“…Post-mortem histopathological features in the lung tissue of patients who died of severe COVID-19 disease demonstrate an extensive inflammatory infiltrate dominated by macrophages in the alveolar lumina [ 2 ]. Thus, infected alveolar macrophages might drive the “cytokine storm” and lead to multiple organ failure in COVID-19 infected patients [ 3 ]. Moreover, systemic cytokine profiles resemble cytokine release syndromes, such as macrophage activation syndrome, in patients with severe COVID-19 disease [ 4 ].…”
mentioning
confidence: 99%